Sosialisasi Zero Food Waste P3K SD Rabbani Purwakarta - Hisny Fajrussalam; Fadia Fazilatun Nisa; Farihah Ayuni; Gina Selvia Rahayu; Rerey Realistiya; Windy Aledya Rosyani (CV. Multi Kreasi Media, 2024)
The zero food waste socialization activity with the theme “From kitchen to nature: The role of family in zero food waste” was held at Rabbani Elementary School Hall, Nagritengah Village, Purwakarta District, Purwakarta Regency. This activity was carried out based on the problem of food waste management and environmental conservation. By targeting parents of students as the target participants of this socialization because of how important the role of the family is from home to start good habits for family members to always understand the concept of zero food waste. This activity goes through two stages, namely 1) the planning stage, where students take strategic steps such as identifying target participants, determining the time and place of implementation, determining the parties who will collaborate to the selection of the main points of material to be delivered by the Purwakarta Regency Environmental Service. 2) Implementation stage, pretest and posttest by parents and delivery of zero food waste material through interactive powerpoint followed by questions and answers conducted to understand more deeply related to the material that has been delivered or that has not been delivered and then continued by collecting feedback from participants to evaluate their understanding of food waste management and behavior change through interviews and also posttest results. The evaluation results show that most parents better understand the importance of managing food waste.